Integrating performance management and enterprise risk management systems : emerging issues and future trends - Spanó, Rosanna (Emerald points., 2022)
Integrating Performance Management and Enterprise Risk Management Systemsoffers a novel understanding of the multifaceted shades that surround the long called-for and yet not realised integration between performance management and enterprise risk management systems.